PRELIMINA RY SCREENING OF LAXATIVE EFFECT OF CUMIN SEEDS IN RATS (Biological Sciences - PJSIR, 2002)
The laxative effect of cumin seeds was investigated. Seeds from the plant, cuminium cyminium were obtained from India .  Their aqueous extract (Aq. extract) was prepared and phytochemical analysis confirmed the presence of saponin s and glycosidic sugars. The extract of cumin, senna suspension and saline solution (as control) were administered to  different groups of rats and the cumulative number  of wet faeces passed  before and  after administration  were counted  for a period   of 24 h. Both the extract of cumin and senna suspension increased the number of wet faeces compared to the control. The  effect of 4g kg- 1 Aq . extract was comparable to 2g kg-1 senna suspension. The Aq. extract also contracted the guinea pig ileum in a dose dependent manner. The contraction  curve  was shifted  to the right  significant  by  atropine (P < 0.05), but was not significantly affected by dibenzyline, hexamethonium or papaverine. The study has thus demonstrated the laxative effect of cumin  seeds.  It may be suggested  that this  effect could  be mediated  by increase in motility  through  stimulation  of muscurinic  receptor s.   However , further work  has to  be done on this to  prove  the mechan ism of  action .